PERANCANGAN MODEL PENDUKUNG KEPUTUSAN PENGADAAN BARANG DENGAN MENGGUNAKAN FUZZY INFERENCE SYSTEM - Viera Astry; Dadang Surjasa; Dedy Sugiarto (JURNAL TEKNIK INDUSTRI, 2017)
Alleriea is a small medium enterprises engaged in the field of providing souvenirs. To increase consumer satisfaction, the company should be able to fullfill consumer demand, The decisions support system in this study is using Fuzzy Inference System with Mamdani type as intuitive and very suitable to be given expert knowledge. This model was designed using MATLAB software and as input will be used to predict the number of requests, the speed of supply and stock condition.The predicted number of demand are made by using forecasting methods by selecting a forecasting model with the smallest MSE value. Based on the comparison of the value of MSE on the ARIMA model and winter, forecasting results obtained by the method of Winter has the smallest MSE value.The verification process is done by looking at the forecasting model with the smallest MSE, the validation process is done to test the normality of residual data. The verification process on fuzzy inference systems is done by testing whether the rules given leave in accordance with the desired output. The validation process using a combination of testing Extreme Test uses a combination of extreme in any condition. The result of this paper is a procurement decision support model using fuzzy inference system which influenced by the demand forecast, stock condition and speed of supply. Designed models have been verified and validated.